Financial Management In Public And Private Junior High Schools - Suwandi SUWANDI; Soewito SOEWITO (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
Adequate financial support is needed to improve the quality of school management. The availability of cost but managed ineffectively and inefficiently does not guarantee the expected quality improvement. Nana Fattah (2000: 90) states that the effort to improve the quality and expansion of education requires at least three major factors, namely (1). Adequacy of educational resources in terms of quality of education personnel, costs and means of learning, (2).The quality of teaching and learning process that can encourage students to learn effectively, and (3).The quality of output in the form of knowledge, attitudes, skills, and values. So adequacy of resources, quality of teaching and learning, and the quality of output will be fulfilled if the required financial support and professional education can be provided in the school.For the smooth management of the school, experts have same opinion and they state that the management can be defined as a process that is: as an action, an activity, or a work that leads to some specific targets, carried out by more than one person in the organization. Management process raises an obligation to carry out managerial jobs or processes, which are divided into three main functions: planning, organizing and controlling.The functions of management consist of planning, implementation and monitoring, thus  based on the information provided before, management has always been demanded to utilize resources effectively and efficiently to achieve the goals of the school. Resources may be classified on physical resources, human resources, financial resources (funding sources), and time resources. So, effective and efficient management of financial resources also contributes to optimize the work of the management.To sharpen the financial management contribution to the smooth running of the school, there is a necessity to describe the functions of the financial management itself and each function will be the key for the school success. In managing school with many challenges and the era of change, the function of financial management becomes very prominent and demands to be known and understood by the Principal, as the person who takes full responsibility for the management of the school.